Self‐Cleaning Surfaces for Heat Recovery During Industrial Hydrocarbon‐Rich Gas Cooling: An Experimental and Numerical Study. Issue 1 (21st September 2018) - Maggiolo, Dario; Seemann, Martin; Thunman, Henrik; Santos, Olga; Larsson, Anton; Sasic, Srdjan; Ström, Henrik
Abstract : The cooling of hydrocarbon‐rich gases in industrial processes often leads to severe fouling, which impedes heat recovery, restricts operative conditions, and increases maintenance costs. The present work investigates whether self‐cleaning surfaces represent a possible solution to overcome this technological bottleneck. Hydrophilic and hydrophobic treatments of compact heat exchanger plates are experimentally and numerically investigated during cooling of syngas produced from biomass gasification. The experimental evidences related to the operation of heat exchanger plates are assessed first, and a deeper insight into the relevant phenomena is thereafter obtained by performing numerical simulations. Our analysis identifies the hydrophobic treatment as the most promising solution and unveils the induced self‐cleaning mechanism: the formation of small‐sized and movable condensed droplets that enhance the collection and removal of gas impurities. These findings open up new routes toward the development of cheaper, more efficient, and sustainable gas cooling systems. © 2018 American Institute of Chemical Engineers AIChE J, 65: 317–325, 2019